Impact of tranexamic acid on clinical and hematologic outcomes following total shoulder arthroplasty. (October 2022) - Kelly, McKayla; Turcotte, Justin; Fowler, M Brook; West, Michaline; Lashgari, Cyrus; Gelfand, Jeffrey
Background: The purpose of this study is to evaluate the impact of intravenous tranexamic acid on clinical and hematologic outcomes after total shoulder arthroplasty. Methods: Retrospective review was conducted for 282 consecutive patients undergoing either anatomic shoulder arthroplasty or reverse total shoulder arthroplasty. Univariate analysis and multivariate linear regression were used to compare outcomes for patients receiving intravenous tranexamic acid with those who did not. Results: Of the 282 patients included in this study, 78 patients received intravenous tranexamic acid and 204 did not. Patients who received intravenous tranexamic acid had significantly lower pre- to postoperative change in hemoglobin and hematocrit, and decreased postoperative drain output. In addition, patients receiving intravenous tranexamic acid were significantly less likely to have a postoperative hematocrit <30. There were no significant differences in length of stay, rate of 30 day hematoma, surgical site infection, deep vein thrombosis, or readmission between groups. Conclusion: Intravenous tranexamic acid is associated with a significant reduction in change in hematocrit and hemoglobin and postoperative drain output after both anatomic and reverse total shoulder arthroplasty. Despite improving hematologic outcomes for these patients, tranexamic acid appears to have little impact on clinical outcomes such as length of stay and 30-day complication rates.